Correlation Between IL-8, C-Reactive Proteins (CRP) and Neutrophil to Lymphocyte Ratio (NLR) as Predictor of Mortality in COVID-19 Patients with Diabetes Mellitus Comorbidity - Iskandar A; Mayashinta DK; Robert R; Samsu N; Endharti AT; Widjajanto E (International Journal of General Medicine, 2023)
Agustin Iskandar,1– 3 Dearikha K Mayashinta,2,3 Robert Robert,3 Nur Samsu,4 Agustina Tri Endharti,2 Edy Widjajanto3 1Doctoral Program in Medical Science, Faculty of Medicine, Universitas Brawijaya/Saiful Anwar General Hospital, Malang, Indonesia; 2Department of Parasitology, Faculty of Medicine, Universitas Brawijaya/Saiful Anwar General Hospital, Malang, Indonesia; 3Department of Clinical Pathology, Faculty of Medicine, Universitas Brawijaya/Saiful Anwar General Hospital, Malang, Indonesia; 4Department of Internal Medicine, Faculty of Medicine, Universitas Brawijaya/ Saiful Anwar General Hospital, Malang, IndonesiaCorrespondence: Agustin Iskandar, Faculty of Medicine, Universitas Brawijaya/Saiful Anwar General Hospital, Malang, Indonesia, Email agustin_almi@ub.ac.idBackground: COVID-19 is caused by SARS-CoV-2 and has a wide range of symptoms. While Diabetes Mellitus (DM) is a common comorbidity in COVID-19 patients, it is the main comorbidity in non-surviving COVID-19 patients. Interleukin-8 (IL-8) is a cytokine that has been correlated with severity and mortality in COVID-19 patients, but its role in COVID-19 patients with DM comorbidity and its relationship with NLR and CRP as markers of inflammation are not yet fully understood.Objective: To investigate the correlation between IL-8, NLR, and CRP in COVID-19 patients with DM comorbidity.Methods: A cross-sectional study was conducted at the Integrated Infectious Disease Installation of Dr. Saiful Anwar Malang Hospital from June to November 2021 using consecutive sampling. IL-8 was measured using the ELISA method with Legendmax® Human IL-8. NLR was measured using flow cytometry, while CRP was measured using the immunoturbidimetric method with Cobas C6000®. Patient outcomes were obtained from medical records.Results: A total of 124 research subjects participated in the study. IL-8 and CRP levels were significantly higher (p < 0.05) in COVID-19 patients with DM comorbidity, and were also significantly higher (p < 0.05) in non-surviving COVID-19 patients. Overall, there was a positive correlation between IL-8 and CRP (r = 0.58, p < 0.05). There was also a positive correlation between IL-8 (r = 0.58; p < 0.05), NLR (r = 0.45, p < 0.05), CRP (r = 0.54, p < 0.05) and mortality in COVID-19 patients with DM comorbidity. The presence of DM comorbidity increased IL-8 levels and aggravated inflammation in COVID-19 patients, thereby increasing the risk of mortality.Conclusion: IL-8, CRP and NLR levels were higher in non-surviving COVID-19 patients with DM comorbidity, indicating that they could serve as good predictors of poor outcomes in this patient population.Keywords: interleukin-8, CRP, NLR, COVID-19